Faktor-Faktor Determinan Kebahagiaan Kerja Karyawan (Studi Kasus Pada PT. Bank Bukopin Tbk. Cabang Manado - Matheos, Meriam Oriliand (Universitas Sam Ratulangi, 2017)
The purpose of this research is to know determinant factors of Â employees work happiness. The results show that determinant factors of employees work happiness is leadership behaviors, individual characteristics, organization trust, organization culture, and work satisfaction. The result supporting theoritical and empirical previous.Keywords: Determinant Factors, Employees Work Happiness, PT. Bank Bukopin.